Marschner's mineral nutrition of higher plants - Marschner, Horst; Marschner, Petra (Academic Press, 2012)
Respected and known worldwide in the field for his research in plant nutrition, Dr. Horst Marschner authored two editions of Mineral Nutrition of Higher Plants. His research greatly advanced the understanding of rhizosphere processes and trace element uptake by plants and he published extensively in a variety of plant nutrition areas. While doing agricultural research in West Africa in 1996, Dr. Marschner contracted malaria and passed away, and until now this legacy title went unrevised. Despite the passage of time, it remains the definitive reference on plant mineral nutrition. Great progress has been made in the understanding of various aspects of plant nutrition and in recent years the view on the mode of action of mineral nutrients in plant metabolism and yield formation has shifted. Nutrients are not only viewed as constituents of plant compounds (constructing material), enzymes and electron transport chains but also as signals regulating plant metabolism via complex signal transduction networks. In these networks, phytohormones also play an important role. Principles of the mode of action of phytohormones and examples of the interaction of hormones and mineral nutrients on source and sink strength and yield formation are discussed in this edition. Phytohormones have a role as chemical messengers (internal signals) to coordinate development and responses to environmental stimuli at the whole plant level. These and many other molecular developments are covered in the long-awaited new edition. Esteemed plant nutrition expert and Horst Marschner's daughter, Dr. Petra Marschner, together with a team of key co-authors who worked with Horst Marschner on his research, now present a thoroughly updated and revised third edition of Marschner's Mineral Nutrition of Higher Plants, maintaining its value for plant nutritionists worldwide. A long-awaited revision of the standard reference on plant mineral nutrition Features full coverage and new discussions of the latest molecular advances Contains additional focus on agro-ecosystems as well as nutrition and quality.